(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In 2015, Europe experienced an unprecedented influx of refugees driven by conflicts, political instability, and socio-economic hardship in the Middle East, North Africa, and other regions. This mass migration has posed a multifaceted challenge for the European Union (EU), leading to social tensions, economic burdens, and political fragmentation among the member states. Germany adopted the Open Door Policy and welcomed over a million refugees. German Chancellor Angela Merkel said, ‘Wir schaffen das’ (We can manage it).